E-maintenance - Holmberg, Kenneth.; Adgar, Adam.; Arnaiz, Aitor.; Jantunen, Erkki.; Mascolo, Julien.; Mekid, Samir. (Springer London, 2010)
E-maintenance is the synthesis of two major trends in todays society: the growing importance of maintenance as a key technology and the rapid development of information and communication technology. E-maintenance gives the reader an overview of the possibilities offered by new and advanced information and communication technology to achieve efficient maintenance solutions in industry, energy production and transportation, thereby supporting sustainable development in society. Sixteen chapters cover a range of different technologies, such as: " new micro sensors; " on-line lubrication sensors; " smart tags for condition monitoring; " wireless communication; and " smart personal digital assistants. E-maintenance also discusses semantic data-structuring solutions; ontology structured communications; implementation of diagnostics and prognostics; and maintenance decision support by economic optimisation. It includes four industrial cases that are both described and analysed in detail, with an outline of a global application solution. E-maintenance is a useful tool for engineers and technicians who wish to develop e-maintenance in industrial sites. It is also a source of new and stimulating ideas for researchers looking to make the next step towards sustainable development.